IMPLEMENTASI MANAJEMEN STRATEGI PENINGKATAN MUTU PEMBELAJARAN PRODI PGMI STAIN AL-FATAH JAYAPURA - Nur'im Septi Lestari (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2020)
In PGMI Program STAIN Al-Fatah Jayapura quality of learning still little bit unsatisfied, because by following the acreditatuon score is C. Based on the fact, implementation management of strategy program PGMI still don't applied yet optimally. This matter affected by number of human resources still limited at homebase of PGMI and theres is not certain duty yet, even head of program education, so all the decision is centered on course department. The aim of this research is to find out the implementation ofmanagement strategy and instructional’s quality of PGMI study program. Based on the result of the data this research has management of strategy in the PGMI Program there were: a.) planning of the learning activity through making learning activity schedule that consist of kind of subjects and list of supported lecturer b.) conducting learning activity in PGMI Program when it conducted as learning schedule and RPS. c.)  controlling/supervising based on : lecturer journal, lecturer teaching daily journal, lecturer absent and lecturer questionaire. d.) evaluation learning activity was applied clearly from lecturer or students. For lecturer through first meeting and the last semester. Meanwhile, evaluation for students through ; active and present score, individual task nor group that given by lecturer, mid-term test, last-term test, and comprehensive test in the end of study.